Front-edge erosion impact on landslide stability: A multi-scale monitoring and numerical simulation case study. - Xiaowei Li; Shimei Wang; Zhihong Fan; Lei Lei; Li Wang; Yuanyuan He; Lin Cheng; Nanshan Deng (PLoS ONE)
Airborne LiDAR enables large-scale landslide displacement field monitoring, yet suffers from complex error sources and lower accuracy than contact measurements. While GPS offers higher precision, it fails to capture overall slope displacement. This study proposes a multi-scale LiDAR-GPS fusion technique for bank slope deformation monitoring, applied to the Shuping landslide. A numerical model based on monitoring data reveals how front-edge erosion impacts landslide stability. The results indicate that: (1)Following the implementation of a correction algorithm that integrated GPS monitoring data with the LiDAR monitoring results, a substantial enhancement in the accuracy of the measurement results was observed. This finding suggests that the integrated airborne LiDAR-GPS-based monitoring method is reliable. (2)The front edge of the Shuping landslide displays differential erosion characteristics, with higher erosion levels observed on the east and west sides of the slope in comparison to the central region. (3)The Shuping landslide as a whole exhibits traction deformation characteristics and the decline in reservoir water level is the main controlling factor that induces landslide deformation. However, the continuous development of front-edge erosion has caused the Shuping landslide's natural stability to decrease. The main reason is that the unloading effect caused by the erosion of the front edge soil redistributes the total stress of the landslide, which is manifested by the tensile stress concentration in the central slope of the landslide, the increase in the maximum total stress, and the increase in deformation.